Risk Factors and Clinical Profile of Seizure in Childhood - Chowdhury, Rumpa Mani; Alam, Badrul; Sharma, Zhulam Das; Das, Krishna Priya; Hossain, Mohammad Zaid; Deb, Sudip Ranjan (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 211-217 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15361